Tourists’ Perception of Destination Image of Chautara: A Study of Cognitive and Affective Dimensions - Mishra, Amit K. (CMC Journal, 2026)
Domestic religious tourism plays a significant role in boosting the local economy and preserving culture. This makes the destination image an important part of tourism planning. Thus, the study investigates cognitive and affective dimensions of destination image of Chautara, Sindhupalchok, specifically in relation to the Gaurati Bhimsen Temple during the annual Jatra. The study is exploratory in nature. A structured questionnaire was used to gather data from 200 domestic tourists visiting Gaurati Bhimsen Temple. The statistical software SPSS was used to analyse the data. Further, the study found a significantly favourable cognitive image (Mean = 4.11) for safety, religious attractions, landscapes, and facilities. However, the affective image was somewhat favourable (Mean = 3.87), reflecting satisfaction and spiritual attachment. Infrastructure and service-related factors, however, were given lower ratings. Thus, the findings of the study suggest that policymakers and marketers should improve service quality and tourist experience to enhance the affective image and support sustainable domestic religious tourism at Chautara.